Police perceptions of ADHD in youth interviewees - Cunial, Kimberley J. (Psychology, crime & law, 2017)
Attention-deficit hyperactivity disorder (ADHD) in witness-victim/suspect interviews holds strong relevance for policing. Four purpose-written vignettes were used to test the extent to which ADHD interviewee behaviour impacts on the work of 46 experienced Australian detectives and their ability to identify ADHD as a likely diagnosis. Detectives reported frequently encountering ADHD-type interviewees in their work; perceiving such interviewees to be at a very significant risk of future contact with the criminal justice system; and perceiving ADHD-type behaviour to exert a highly significant impact on interviewing time efficiency as well as quality. Detectives gave highly significant ratings of ADHD as a likely explanation of vignettes describing ADHD-type behaviour for witness-victims as well as suspects. However, they could not identify ADHD as the most likely explanation over and above other possibilities. Implications are discussed in terms of a rationale for future research targeting police awareness and training needs in ADHD.